Synthesis of Symmetrical Tetrameric Conjugates of the Radiolanthanide Chelator DOTPI for Application in Endoradiotherapy by Means of Click Chemistry - Wurzer, Alexander; Vágner, Adrienn; Horváth, Dávid; Fellegi, Flóra; Wester, Hans-Jürgen; Kálmán, Ferenc K.; Notni, Johannes (Frontiers in Chemistry, 2018)
Due to its 4 carbonic acid groups being available for bioconjugation, the cyclen tetraphosphinate chelator DOTPI, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrakis[methylene(2-carboxyethylphosphinic acid)], represents an ideal scaffold for synthesis of tetrameric bioconjugates for labeling with radiolanthanides, to be applied as endoradiotherapeuticals. We optimized a protocol for bio-orthogonal DOTPI conjugation via Cu(I)-catalyzed Huisgen-cycloaddition of terminal azides and alkynes (CuAAC), based on the building block DOTPI(azide)4. A detailed investigation of kinetic properties of Cu(II)-DOTPI complexes aimed at optimization of removal of DOTPI-bound copper by transchelation. Protonation and equilibrium properties of Ca(II)-, Zn(II) and Cu(II)-complexes of DOTPI and its tetra-cyclohexylamide DOTPI(Chx)4 (a model for DOTPI conjugates) as well as kinetic inertness (transchelation challenge in the presence of 20 to 40-fold excess of EDTA) were investigated by pH-potentiometry and spectrophotometry. Similar stability constants of CaII-, ZnII and CuII-complexes of DOTPI (logK(CaL)=8.65, logK(ZnL=15.40, logK(CuL)=20.30) and DOTPI(Chx)4 (logK(CaL)=8.99, logK(ZnL)=15.13, logK(CuL)=20.42) were found. Transchelation of CuII-complexes occurs via proton-assisted dissociation, whereafter released Cu(II) is scavenged by EDTA. The corresponding dissociation rates (kd=25×10−7 and 5×10−7 s−1 for Cu(DOTPI) and Cu(DOTPI(Chx)4), respectively, at pH 4 and 298 K) indicate that conjugation increases the kinetic inertness by a factor of 5. However demetallation is completed within 4.5 and 7.2 hours at pH 2 and 25 °C, respectively, indicating that CuII removal after formation of CuAAC can be achieved in an uncomplicated manner by addition of excess H4EDTA. For proof-of-principle, tetrameric DOTPI conjugates of the prostate-specific membrane antigen (PSMA) targeting motif Lys-urea-Glu (KuE) were synthesized via CuAAC as well as dibenzo-cyclooctine (DBCO) based, strain-promoted click chemistry (SPAAC), which were labeled with Lu-177 and subsequently evaluated in vitro and in SCID mice bearing subcutaneous LNCaP tumor (PSMA+ human prostate carcinoma) xenografts. High affinities (3.4 and 1.4 nM, respectively) and persistent tumor uptakes (approx. 3.5% 24 h after injection) confirm suitability of DOTPI-based tetramers for application in targeted radionuclide therapy.